Manajemen Pengelolaan Pendingin Ruangan Berbasis QR Code Terintegrasi - Mardi Wasono; Aris Fakhrudin; Sudarmanto Sudarmanto; David Julian Nggebu; Wibi Laksono Wijaya (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
The management of air conditioning (AC) infrastructure in the Faculty of Mathematics and Natural Sciences, Gadjah Mada University (FMIPA UGM) is still carried out separately by each unit, resulting in problems such as lack of maintenance, lack of asset data integration, and low human resource work efficiency. This study aims to design and implement an air conditioning management information system based on Quick Response (QR) Code technology that is integrated with smartphone devices and internet networks. The research methods include needs analysis, web-based system design, implementation using a MySQL database and the CodeIgniter 4 framework, and system functional testing. The results of the study indicate that the developed system is able to integrate air conditioning asset data, facilitate real-time damage reporting through QR Code scanning, and provide automatic notifications to admins and those in charge of related units. The implementation of this system is proven to increase the efficiency of asset management and accelerate the process of handling air conditioning problems in the FMIPA UGM environment. Keywords: Management, Air Conditioning, Human Resource Efficiency, QR Code.